The Effect of Complex Korean Medical Treatment with Acupotomy on Irritable Bowel Syndrome: A Case Report - Baek Ki Min; Joon Soo Jin; Do Eun Lee; Won Bin Shin; Jin Hyeon Shin; In Ae Youn (MEDrang Inc., 2020)
The effects of complex Korean medicine treatment including acupotomy, on irritable bowel syndrome (IBS) are reported in this case study. A 54-year-old woman with diarrheal symptoms that alternatively improved and worsened for many years and worsening abdominal pain visited the emergency room and was diagnosed with IBS; she was admitted for approximately 2 weeks at the Acupuncture and Moxibustion Department of National Medical Center (NMC). Numerical rating scale (NRS), irritable bowel syndrome?quality of life (IBS-QOL), and gastrointestinal symptom rating scale (GSRS) scores were evaluated on the day of hospitalization, midway through the hospitalization period, and on the day of discharge. Abdominal pain was measured daily using NRS, and the score decreased from 8 at admission to 0 at discharge. The IBS-QOL percentile score improved from 42 points to 100 points. The total GSRS score also improved, from 30 points to 2 points. These results suggest that complex Korean medicine treatment with acupotomy, is useful for treating internal diseases, such as IBS, as well as musculoskeletal disorders.